Using ChatGPT as a Tutor to learn Mathematics Application Program - Manik, Efron; Sihombing, Dame Ifa; Sianturi, Rianti; Simbolon, Totaria (International Journal of Research in Education, 2024)
The ability of ChatGPT to understand conversational context and provide relevant responses makes it very useful in human-computer interactions. ChatGPT can be a very useful tool for mathematics teachers in their role as tutors to learn and teach various applications related to mathematics. In this digital era, mathematical applications and software like GeoGebra, Matlab, Augmented Reality, and SPSS are becoming increasingly important in teaching and learning mathematics. ChatGPT can help teachers understand how to use these tools by providing detailed explanations, tutorials, and examples of their application in teaching. This research aims to determine the effectiveness and efficiency of ChatGPT in helping teachers understand and apply technologies such as GeoGebra, Matlab, Augmented Reality, and SPSS. Participants in this case study research consisted of 5 teachers. The categories of participant questions asked to ChatGPT included (1) General explanation of the application, (2) How to download the application, (3) Equipment specifications required, (4) General use of the application, and (5) Requesting sample commands in the application. The results of this study indicate that participants will successfully use ChatGPT as a tutor for learning Mathematics Application Programs if they have the necessary equipment specifications required by the applications and are able to download the applications.